ANALISIS GANGGUAN KONDUKTOR TERBUKA (ONE-CONDUCTOR OPEN FAULT) PADA SISTEM TENAGA LISTRIK - Muhammad Adam (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2013)
This studi discusses the interference of the pahse conductor open same disorders that occur may een pase a danger to the operator and the equipment of the power system.